Analisis Teks Fungsional dari Sumpah Insinyur: Metafungsi dan Karakteristik Bahasanya: Metafungsi dan Karakteristik Bahasa dari Sumpah Insinyur - Rita Darmayanti (LP2M IAIN Sultan Amai Gorontalo, 2019)
This paper aims at investigating the language structure of the oath for engineers in the light of Systemic Functional Linguistics and examining how the oath is textualized to accomplish its roles and objectives as the guiding principle which sets the ideals and obligation of professional engineers. Hence, the main objective of this study is to identify the pattern of the text’s structure by analyzing its metafunctions comprising the textual, interpersonal, and ideational functions. The main data used in this study is the text of oath for engineers as subscribed by the members of professional engineers in USA and Canada. The results of data analysis showed that the text has special features characterizing the genre of oath and its purpose as indicated by 1) the predominance of declarative clauses, 2) the equal usage of marked and unmarked themes representing the setting and reaction phases in the text, 3) the typical form of zig-zag pattern of the thematic organization, and 4) the dominant use of material processes indicating that the text construes the world more in terms of action with engineers at its center, 5) the validity of proposition of the oath for the present time when the engineers subscribe to the oath and to the actual situation for the future time as indicated by the tense of the clauses in the text. Thus, unfolding the discourse of oath in English for engineering class is beneficial to increase learning interactions in which reading is treated as the focus of the teaching as well as enhancing students’ individual development as a part of character education.